2012
DOI: 10.1080/13607863.2011.644262
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of psychotropic medication use among older adults in Israel: Cross-sectional and longitudinal findings from two cohorts a decade apart

Abstract: Objectives To assess: 1) changes in use of psychotropic medications across two cohorts, ten years apart, of community-dwelling elderly and the socio-demographic, physical and mental health correlates of their use; and 2) changes in psychotropic medication use over 3.5 years follow-up. Methods Data were taken from two national surveys of the Israeli Jewish population aged 75–94, which respectively sampled two cohorts in 1989 (n=1200) and again in 1999 (n=421). Psychotropic medications were assessed from the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
16
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 37 publications
7
16
1
Order By: Relevance
“…However, this finding was consistent with some of the latest international studies 19,20 . BZD are drugs that have an increased risk of dependence and whose chronic use had already been detected in Brazilian studies 21 , ensuing concern.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, this finding was consistent with some of the latest international studies 19,20 . BZD are drugs that have an increased risk of dependence and whose chronic use had already been detected in Brazilian studies 21 , ensuing concern.…”
Section: Discussionsupporting
confidence: 82%
“…In the latter's case, it is possible that the pattern of current consumption is distinct from that of 2003. However, it is worth noting the similarity between our results and those of recent international studies 19,20 , as well as the fact two of the most used medication (amitriptyline and diazepam) are included in the list of drugs encompassed in basic pharmaceutical care, directed to conditions seen as priorities in basic health care 32 .…”
Section: Discussioncontrasting
confidence: 38%
“…This difference can be explained by the increased use of antidepressants worldwide 32 and also to the prescriptive habits of Brazilian physicians. The concomitant use of antidepressant can be a consequence of depressive disorder, anxiety disorder or improper use of BZD 17,18,23,26 , which could also be related to emotional or nervous disorder 16 , or depression can be associated to physical, mental and psychosocial problems 30 , making diagnosis difficult. Another study reported self-assessment of emotional or nervous disorder significantly associated to the use of BZD (OR: 6.66; CI95%: 5.09-8.71), but the consumption of antidepressants was not assessed 16 , unlike the findings of Monongahela Valley, EUA, where depressive symptoms were not significantly associated to the use of BZD 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted with the general population in a telephone interview in France found association between use of BZD and aging [35-44 years -OR: 3.1; (CI95%: 1.8-5.1); 45-59 years -OR: 6.1 (CI95%: 3.8-9.7) and 60 years or older -OR: 11.1 (CI95%: 7.1-17.5)] 28 , as in the present study. Analysis of the period of time of use of these medications showed that individuals aged over 75 years were more likely to use BZD for a long period 24,29 and some authors claim that psychotropic drugs are the most suitable for this age group 7,30 . However, a population-based survey with elderly on BZD use did not detect age as a factor associated to the habit of using BZD (p > 0.050) 15,16,18 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been associated with medical and psychiatric conditions and with impaired daily functioning, cognitive decline, poor health‐related quality of life, risk of falls and hip fractures, and all‐cause mortality . Furthermore, the use of hypnotic medications for the treatment of insomnia is most prevalent and most chronic in elderly adults and has been associated with depression and traumatic life events, poor functional status, and risk of injury …”
mentioning
confidence: 99%